ERP evidence of attentional somatosensory processing and stimulus-response coupling under different hand and arm postures - Kida, Tetsuo; Kaneda, Takeshi; Nishihira, Yoshiaki (Frontiers in Human Neuroscience, 2023)
We investigated (1) the effects of divided and focused attention on event-related brain potentials (ERPs) elicited by somatosensory stimulation under different response modes,(2) the effects of hand position (closely-placed vs. separated hands) and arm posture (crossed vs. uncrossed forearms) on the attentional modulation of somatosensory ERPs, and (3) changes in the coupling of stimulus-and response-related processes by somatosensory attention using a single-trial analysis of P300 latency and reaction times.Electrocutaneous stimulation was presented randomly to the thumb or middle finger of the left or right hand at random interstimulus intervals (700-900 ms). Subjects attended unilaterally or bilaterally to stimuli in order to detect target stimuli by a motor response or counting. The effects of unilaterally-focused attention were also tested under different hand and arm positions. The amplitude of N140 in the divided attention condition was intermediate between unilaterally attended and unattended stimuli in the unilaterally-focused attention condition in both the mental counting and motor response tasks. Attended infrequent (target) stimuli elicited greater P300 in the unilaterally attention condition than in the divided attention condition. P300 latency was longer in the divided attention condition than in the unilaterally-focused attention condition in the motor response task, but remained unchanged in the counting task. Closely locating the hands had no impact, whereas crossing the forearms decreased the attentional enhancement in N140 amplitude. In contrast, these two manipulations uniformly decreased P300 amplitude and increased P300 latency. The correlation between single-trial P300 latency and RT was decreased by crossed forearms, but not by divided attention or closely-placed hands. Therefore, the present results indicate that focused and divided attention differently affected middle latency and late processing, and that hand position and arm posture also differently affected attentional processes and stimulus-response coupling.